Pengaruh Wordwall terhadap Hasil Belajar dan Karakter Cinta Tanah Air pada Mata Pelajaran Pendidikan Pancasila di SD N Adisana 04 - Yuli Puji Hutami (Journal on Education, 2024)
This research aims to determine the effect of word walls on learning outcomes and the character of patriotism in Pancasila education subjects. The approach taken in this research is quantitative in the form of a true experimental design with a posttest only-control design type. The population in this research is class IV students at SD N Adisana 04 and SD N Dukuhturi 02 with a total of 60 students in the 2023/2024 academic year. With the sampling technique, namely saturated sampling, 60 students were selected as research samples, consisting of 30 class IV students at SDN Adisana 04 as the experimental class and 30 class IV students at SDN Dukuhturi 02 as the control class. The data collection instrument for learning outcomes was carried out using multiple choice questions, for the character of patriotism it was carried out using a self-assessment sheet in the form of a questionnaire. Results obtained (1) The learning results from the t test results obtained a sig value of 0.019 or sig < 0.05, so that HO was rejected and Ha was accepted. This means that the word wall learning model has an influence on Pancasila education learning outcomes. (2) The character of love for one's country from the t test results obtained a sig value of 0.536 > 0.05, which means there is no influence from the use of word wall learning media on the character of love for one's country where Ho is accepted and Ha is rejected. So descriptively there is an influence of the word wall on learning outcomes in Pancasila education subjects and there is no influence of the word wall on the character of love for the country in students.